Superconformal Bottom-Up Gold Deposition in High Aspect Ratio Through Silicon Vias - Josell, D. (J Electrochem Soc, 2017)
This work presents superconformal, bottom-up Au filling of high aspect ratio through silicon vias (TSVs) along with a predictive framework based on the coupling of suppression breakdown and surface topography. The work extends a previous study of superconformal Au deposition in lower aspect ratio TSVs. Deposition was performed in a Na(3)AuSO(3) electrolyte containing a branched polyethyleneimine (PEI) deposition-rate suppressing additive. Voltammetric measurements using a rotating disk electrode (RDE) were used to assess the impact of the PEI suppressor concentration and transport on the rate of metal deposition, enabling the interplay between metal deposition and suppressor adsorption to be quantified. The positive feedback associated with suppression breakdown gives rise to an S-shaped negative differential resistance (S-NDR). The derived kinetics for suppressor adsorption and consumption were used in a mass conservation model to account for bottom-up filling of patterned features. Predictions, including the impact of deposition potential and additive concentration on feature filling, are shown to match experimental results for filling of TSVs. This further generalizes the utility of the additive derived S-NDR model as a predictive formalism for identifying additives capable of generating localized, void-free filling of TSVs by electrodeposition.